2014
DOI: 10.1111/evo.12381
|View full text |Cite
|
Sign up to set email alerts
|

Mate Preference for a Phenotypically Plastic Trait Is Learned, and May Facilitate Preference-Phenotype Matching

Abstract: Fixed, genetically determined, mate preferences for species whose adult phenotype varies with rearing environment may be maladaptive, as the phenotype that is most fit in the parental environment may be absent in the offspring environment. Mate preference in species with polyphenisms (environmentally dependent alternative phenotypes) should therefore either not focus on polyphenic traits, be polyphenic themselves, or learned each generation. Here, we test these alternative hypotheses by first describing a fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 47 publications
0
70
0
Order By: Relevance
“…Nevertheless, in our study when the OSR was biased towards females, sex role did not seem to be totally reversed as female choosiness appeared to increase with increasing densities: females escaped more often and more rapidly from male mating attempts with increasing density. Therefore, mutual mate choice appeared to vary with density under the female-biased sex ratio in our study, suggesting that mutual mate choice in B. anynana occurs in the wet seasonal form and not only at the level of the seasonal sex role reversal of the species (Prudic et al, 2011;Westerman, Chirathivat, et al, 2014).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Nevertheless, in our study when the OSR was biased towards females, sex role did not seem to be totally reversed as female choosiness appeared to increase with increasing densities: females escaped more often and more rapidly from male mating attempts with increasing density. Therefore, mutual mate choice appeared to vary with density under the female-biased sex ratio in our study, suggesting that mutual mate choice in B. anynana occurs in the wet seasonal form and not only at the level of the seasonal sex role reversal of the species (Prudic et al, 2011;Westerman, Chirathivat, et al, 2014).…”
Section: Discussionmentioning
confidence: 52%
“…OSR, Arnqvist, 1992;Kokko et al, 2012;Krupa & Sih, 1993;density, Jirotkul, 1999b;Mills & Reynolds, 2003;Pomfret & Knell, 2008;Rowe et al, 1994). In B. anynana, there has long been a general agreement that female choice should prevail in the wet seasonal form (van Bergen et al, 2013;Brakefield et al, 2001;Costanzo & Monteiro, 2007;Frankino, Zwaan, Stern, & Brakefield, 2007;Nieberding et al, 2008Nieberding et al, , 2012Prudic et al, 2011;Robertson & Monteiro, 2005;Westerman, Chirathivat, Schyling, & Monteiro, 2014;Westerman, Drucker, & Monteiro, 2014;Westerman, HodginsDavis, Dinwiddie, & Monteiro, 2012;Westerman & Monteiro, 2013). This is notably based on the facts that females do reject courting males, rarely mate more than once in the field and in the laboratory (van Bergen et al, 2013;Brakefield et al, 2001;Brakefield & Reitsma, 1991;Joron & Brakefield, 2003;Nieberding et al, 2008Nieberding et al, , 2012, and gain neither direct benefits (no evidence for nuptial gifts, Ferkau & Fischer, 2006;M€ olleman, Zwaan, & Brakefield, 2004; but see Prudic et al, 2011;Westerman, Drucker, et al, 2014, who suggest that females may receive a beneficial nuptial gift from dry season males) nor fitness benefits from multiple matings while suffering survival costs (Fischer, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, male B. anynana have been shown to learn preferences to mate with particular phenotypes of females with dorsal hind wing eyespot numbers, depending on pre‐mating experience with that phenotype (Westerman et al . ). It is suggested that in this system plastic mate preferences, rather than pre‐existing mating biases, allow male B. anynana butterflies the opportunity to choose the best mate in a highly fluctuating environment season, with social experiences providing the basis for learning.…”
Section: Discussionmentioning
confidence: 97%
“…Bicyclus anynana is also a species where adults have previously been shown to learn a variety of different wing patterns (Westerman et al. , ; Westerman and Monteiro ) as well as pheromone odors (Dion et al. ).…”
mentioning
confidence: 99%